The determinants of work-life balance among nurses in public hospital in Klang Valley - Shamshir Ali, Nazri Harris; Syed Ahmad, Sharifah Fazirah; Che Nawi, Nur Raihan; Sabar, Sarinah; Ali Husin, Liatul Izian (International Foundation for Research and Development, 2023)
The need to have a healthy work-life balance is generally recognized across several professional domains. The present investigation was carried out within a public health institution situated in the Klang Valley region. The objective of this study is to investigate the impact of workload, time management, and work environment on the work-life balance of nurses, who serve as frontline healthcare professionals. The research utilized purposive sampling as one of the quantitative research methods. Online distribution was utilized as the means of data collection. A grand total of 276 questionnaires were appropriately completed and afterward returned. The findings indicate that workload negatively impacts employee work-life balance when compared to aspects such as time management and work environment. All the variables found have a significant impact on employees work-life balance in different positive and negative relationships.